Applying Arcaro’s Total Quality Management (TQM) Principles In Strategic Efforts To Enhance Educational Service Quality: Introduction, Methodology, Findings, Discussion, Conclusion, References - Rusda, Rusda; Rahmani Hafizi; Suyoto; Aslamiah; Celiya Cinantya (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
Total The abstract is well structured and written in clear academic language; however, this revision strengthens the theoretical contribution and novelty of the research. Total Quality Management (TQM) has evolved into one of the most influential paradigms for achieving excellence in education. In the 21st century, educational institutions are challenged to provide services that are student-centered, data-driven, and responsive to stakeholder expectations. This study aims to critically analyze the strategic relevance and theoretical contribution of Arcaro’s TQM principles in enhancing educational service quality. By employing a library research method, this study synthesizes findings from national and international scholarly literature, including journals, books, and prior studies on TQM implementation in education. The analysis reveals that Arcaro’s TQM framework not only aligns with global educational quality standards but also introduces a pedagogical dimension often absent in conventional management models. Its focus on leadership commitment, stakeholder participation, data-based evaluation, and continuous improvement provides a holistic structure for institutional transformation. Theoretically, this study contributes to the modernization of educational quality management by integrating Arcaro’s human-centered approach emphasizing ethical leadership, collaborative culture, and learner empowerment into contemporary educational contexts. Practically, the adaptation of Arcaro’s TQM principles offers a new strategic perspective for developing sustainable quality systems in both schools and higher education institutions. Despite challenges such as limited resources, bureaucratic rigidity, and resistance to change, effective leadership and adaptive governance remain key to successful implementation. In conclusion, Arcaro’s TQM framework provides a comprehensive and contextually adaptable model that bridges management theory and educational innovation, advancing a culture of continuous improvement and stakeholder satisfaction in the global education landscape.